Swedish electoral data: Local elections 1976 - Statistics Sweden (Statistics Sweden, 1989)
Election returns for all electoral districts in Sweden. Includes information on the total number of persons entitled to vote in the local elections, and separately the number of immigrants who have not become citizens of Sweden, but were entitled to vote in this election according to a new law, number of persons who actually voted, and number of valid and invalid ballots respectively.

Valresultat för samtliga valdistrikt vid kommunalvalen 1976-2006. Innehåller uppgifter om det totala antalet röstberättigade, antal röstande, antal giltiga respektive ogiltiga valsedlar samt antalet poströster. Dessutom finns uppgifter om antalet röster för de större partierna.
Svenska valdata: Kommunalvalen 1976
Keywords: elections; val; local government elections; kommunalval; election data; valdata; Elections; Val; Social Sciences; Samhällsvetenskap